2008
DOI: 10.1080/10934520802330057
|View full text |Cite
|
Sign up to set email alerts
|

The impact of using biodiesel/marine gas oil blends on exhaust emissions from a stationary diesel engine

Abstract: The purpose of this work was to investigate the impact of marine gas oil (MGO)/biodiesel blends on the exhaust emissions and fuel consumption in a single cylinder, stationary, diesel engine. Three different origins of biodiesel were used as the blending feedstock with the reference MGO, at proportions of 5 and 10% by volume. Methyl esters were examined according to the automotive FAME standard EN 14214. The baseline MGO and biodiesel blends were examined according to ISO 8217:2005 specifications for the DMA ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
10
0
2
Order By: Relevance
“…A similar NOx increase has been reported for SVO blends with diesel [22,25]. Published literature on SVO/diesel blends in diesel engines indicates this NOx increase is primarily due to non-uniform spraying and burning of fuel [3,22,25].…”
Section: Reduction In Noxsupporting
confidence: 60%
“…A similar NOx increase has been reported for SVO blends with diesel [22,25]. Published literature on SVO/diesel blends in diesel engines indicates this NOx increase is primarily due to non-uniform spraying and burning of fuel [3,22,25].…”
Section: Reduction In Noxsupporting
confidence: 60%
“…Figure 13(a) exhibits CO emissions with the reference diesel and five oxygenated blends. As seen in Figure 13(a), as a whole, CO emissions are higher for higher engine loads, which are generally typical of all internal combustion engines due to decrease in air-fuel ratios with the increase in engine loads [43]. From Figure 13 Published literature [6,7,43,48] showed lower CO emissions with oxygenated fuels.…”
Section: Ubhc Emissionsmentioning
confidence: 81%
“…Relative to the reference diesel, the reductions in UBHC by oxygenated blends are in the range of 30-55% (Figure 12(c)). Karavalakis et al [43] reported lower UBHC emissions with methyl esters at all engine loading conditions. Nabi et al [47] claimed lower UBHC emissions with an oxygenated blend and an ester blend.…”
Section: Ubhc Emissionsmentioning
confidence: 93%
See 1 more Smart Citation
“…com um álcool de cadeia curta (etanol e/ou metanol) na presença de um catalisador ácido (HCL -ácido clorídrico) ou básico (NaOH -Hidróxido de sódio), obtendo como produto final o éster etílico e/ou metílico de acordo com o álcool utilizado e o subproduto glicerina que pode ser refinado mais adiante para o uso em indústrias farmacêuticas e cosméticas Graboski et al, 1998;Parente, 2003 (Di et al, 2009;Lapuerta et al, 2008b). As diferenças entre as emissões do combustível diesel e biodiesel variam dependendo do motor, combustível, condição de operação (Bunger et al, 2000a) e do tipo do óleo biodiesel utilizado (Karavalakis et al, 2008 Freitas et al, 2004;Farhat et al, 2005;Arbex et al, 2009), morbidade e mortalidade cardiovascular (Cançado et al, 2006;Cendon et al, 2006. Sendo que os eventos cardiovasculares fatais ocorrem no mesmo dia da exposição ao MP Braga et al (2001).…”
Section: Combustíveis Diesel E Biodieselunclassified